Physiological Significance of Thromboxane A2 Receptor Dimerization - Masako Sasaki; Katsutoshi Miyosawa; Satoko Ohkubo; Norimichi Nakahata (Journal of Pharmacological Sciences, 2006)
Abstract.: The thromboxane A2 receptor (TP), one of the G protein-coupled receptors (GPCRs), consists of two splicing variants, TPα and TPβ, which differ in their C-terminal regions. In the present study, we investigated whether TPα and TPβ formed homo- or hetero-dimers and whether the dimerization changed the function of TP. The immunofluorescent analysis using human embryonic kidney (HEK) 293 cells expressing either FLAG-tagged TPα or TPβ showed that TPα is mainly distributed on plasma membranes and TPβ existed on plasma membranes and within the cells. Co-immunoprecipitation analysis using HEK293 cells expressing both TPα and TPβ showed that TPα and TPβ formed homo- and hetero-dimers. U46619, a TP agonist, caused phosphoinositide hydrolysis and elevation of [Ca2+]i in a concentration-dependent manner in Chinese hamster ovary (CHO) cells expressing TPα or TPβ. The responses were observed to a greater extent in the cells expressing TPα than TPβ. In the cells expressing both TPα and TPβ, U46619-induced responses were observed to a lesser extent than in the cells expressing TPα alone. Furthermore, [3H]SQ29548 binding showed that the level of the cell surface expression of TP was the following order: the cells expressing TPα > TPα and β > TPβ. These results indicate that TPα and TPβ formed homo- and hetero-dimers, and TP-mediated signaling may be regulated by the hetero-dimer. Keywords:: thromboxane A2 receptor, thromboxane A2 receptor (TP) α, TPβ, dimerization, phosphoinositide hydrolysis